HUBUNGAN KARAKTERISTIK MASYARAKAT DAN STATUS KESEHATAN RUMAH PADA MASYARAKAT DESA ANDONGREJO DUSUN BANDEALIT KECAMATAN TEMPUREJO KABUPATEN JEMBER - Moelyaningrum, Anita Dewi; Zulkarnain, Elfian; D.M., Nungki Yuliana (FKM - UNEJ, 2007)
House have a lot of functions such as phisic and social and mental growth. The purpose of this research is to study the association between society characteristic (level of education, knowledge, income, and amount of family member) and health status of house. Cross sectional study design was conducted in Bandealit, Jember. Data collected by interviewed to 79 samples and observation to their house by using health house card. The samples were selected by proportional random sampling. The research was to be analyzed with chi square test. Result of research indicate that is relationship between level education and health status of house (significantly, p=0.037), mount family income and health status of house (significanty, p=0.0001), but there no relationship between level of knowledge and health status of house (p=0.587), amount of family member and health status of house (p=1.00) Conclusion ,the research show that there is association between society characteristic and health status of house from education factor and income, but there is no association with knowledge factor and amount of family member. Government should rebuild a healthy house for village community. Keywords : society characteristic ,health house card, health status of house